2023
DOI: 10.3389/fcvm.2022.1019435
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA LOC100911717-targeting GAP43-mediated sympathetic remodeling after myocardial infarction in rats

Abstract: ObjectiveSympathetic remodeling after myocardial infarction (MI) is the primary cause of ventricular arrhythmias (VAs), leading to sudden cardiac death (SCD). M1-type macrophages are closely associated with inflammation and sympathetic remodeling after MI. Long noncoding RNAs (lncRNAs) are critical for the regulation of cardiovascular disease development. Therefore, this study aimed to identify the lncRNAs involved in MI and reveal a possible regulatory mechanism.Methods and resultsM0- and M1-type macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In addition, RNA pull-down assays demonstrated that LOC10 might interact with growth-associated protein 43 (GAP43). The results further supported the reduction in GAP43 expression and in VA incidence after LOC10 knockdown in rat hearts following adeno-associated virus (AAV) injection [90]. This study demonstrated the role of the LOC10/GAP43 axis in the regulation of VA.…”
Section: Ventricular Arrhythmiassupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, RNA pull-down assays demonstrated that LOC10 might interact with growth-associated protein 43 (GAP43). The results further supported the reduction in GAP43 expression and in VA incidence after LOC10 knockdown in rat hearts following adeno-associated virus (AAV) injection [90]. This study demonstrated the role of the LOC10/GAP43 axis in the regulation of VA.…”
Section: Ventricular Arrhythmiassupporting
confidence: 69%
“…NcRNAs are important regulators of inflammation and sympathetic remodeling following MI. Li et al identified and characterized lncR-NAs that are potentially implicated in VA following MI [90]. In their study, differentially expressed lncRNAs were identified by RNA-seq on nonactivated M0-and proinflammatory M1-type macrophages.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%